Proteomics research on forest trees, the most recalcitrant and orphan plant species. - Abril, Nieves; Gion, Jean-Marc; Kerner, René; Müller-Starck, Gerhard; Cerrillo, Rafael M. Navarro; Plomion, Christophe; Renaut, Jenny; Valledor, Luis; Jorrin-Novo, Jesús V. (Phytochemistry, 2011)
The contribution of proteomics to the knowledge of forest tree (the most recalcitrant and almost forgotten plant species) biology is being reviewed and discussed, based on the author's own research work and papers published up to November 2010. This review is organized in four introductory sections starting with the definition of forest trees (1), the description of the environmental and economic importance (2) and its derived current priorities and research lines for breeding and conservation (3) including forest tree genomics (4). These precede the main body of this review: a general overview to proteomics (5) for introducing the forest tree proteomics section (6). Proteomics, defined as scientific discipline or experimental approach, it will be discussed both from a conceptual and methodological point of view, commenting on realities, challenges and limitations. Proteomics research in woody plants is limited to a reduced number of genera, including Pinus, Picea, Populus, Eucalyptus, and Fagus, mainly using first-generation approaches, e.g., those based on two-dimensional electrophoresis coupled to mass spectrometry. This area joins the own limitations of the technique and the difficulty and recalcitrance of the plant species as an experimental system. Furthermore, it contributes to a deeper knowledge of some biological processes, namely growth, development, organogenesis, and responses to stresses, as it is also used in the characterization and cataloguing of natural populations and biodiversity (proteotyping) and in assisting breeding programmes.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 21353265
Keywords: Forest tree proteomics; forest trees; Plant proteomics; Woody plants